The physiology of the highly trained female endurance runner - Burrows, M.; Bird, S. (Sports Medicine, 2000)
Continuing improvements in the performance of female endurance runners and increasing levels of participation have generated the need to know more about the physiology of this group. Specific research is needed in this area, as data referring to male endurance runners cannot legitimately be applied to the female endurance runner because of their markedly different physiological and hormonal profiles. Recent developments in our understanding of an athlete's physiology (mainly in relation to the male endurance runner) have revealed new areas of interest that need to be assessed with specific reference to the female athlete. Relatively little attention has been directed towards identifying the major physiological characteristics of the highly trained/elite female endurance runner in general, and that which has been published on such factors and the effects of the menstrual cycle have produced equivocal results. Moreover, the impact of such training upon the menstrual cycle and endurance running performance is a controversial area, especially when assessing its subsequent impact on health-related issues. Reports of the condition referred to as the 'female athlete triad' have increased in recent years, with a decrease in bone mineral density predisposing the female athlete to increased risks of stress fractures. The aetiology of this triad is multifactorial, with such risk factors including nutrition, menstrual status, training intensity and frequency, body size and composition and psychology/physical stress. However, research limitations and flaws have lead to controversy in the literature regarding the immediate and long term effects of the triad on the female athlete. Likewise, the effects of the oral contraceptive pill on health and endurance performance also remain elusive, with a dearth of research pertaining to how oral contraceptive agents can aid athletic performance and the long term health of the female athlete. The purpose of this paper is to critically appraise the existing literature to provide a current review of the physiological scientific knowledge base in relation to the female athlete, health, training and performance, with suggestions for future areas of research. It is well known that certain menstrual and health-related performance factors of the female athlete, that is, physiological predictors of performance and body fat, have been extensively investigated over the last 30 years. However, a variety of methodological flaws and inconsistencies are present within the research and thus only the most prominent and well controlled studies within this area over the past 30 years will be referred to.